Interaction between pedestrians and automated vehicles: Perceived safety of yielding behaviors and benefits of an external human–machine interface for elderly people - Bellet, Thierry; Laurent, Sébastien; Bornard, Jean-Charles; Hoang, Isabelle; Richard, Bertrand (Frontiers in Psychology, 2022)
This study focuses on Automated Vehicles (AVs) interactions with pedestrians during road crossing situations. A dual-phases experiment was designed: one from the pedestrian’s perspective and the other one from the AV passenger’s point of view. Eight AV behaviours to yield were investigated. Participants’ task was to assess the safety each one of these yielding behaviours. Moreover, an external HMI (eHMI) was designed to support them in these interactions. Forty participants were involved in this experiment (50% females, 20 young versus 20 elderly). Results obtained show significant differences between old and young participants: elderly people have not the same way to perceive and assess the safety of the yielding behaviours from “the inside” and from “the outside” of the car. Conversely, young participants assessed AV behaviours similarly whether as pedestrians or as AV passengers. When considering benefits introduced by the eHMI, it significantly reduces differences between old and young participants and tends to harmonize their safety assessments: with to the eHMI, elderly people are more able to adequately perceive and assess the safety/dangerousness of the AV braking manoeuvers, and their safety judgments become at last quite similar to those of young participants. Moreover, the eHMI increases participants’ Acceptance of AV and reduces their concerns about their future interactions with AV as a pedestrian, especially for elderly people.